Obtainment of biofunctional ingredients from whey protein concentrates. - OZORIO, L. (2019)
Tese (doutorado) em Ciências - Universidade Federal do Rio de Janeiro, Instituto de Química. Orientadora: Lourdes Maria Correa Cabral (CTAA). Coorientadora: Caroline Mellinger Silva (CTAA). Rio de Janeiro, 2019.